The Effect of Board Size, Institutional Ownership and Insolvency Risk on Financial Distress Before and During Covid-19 - Ivena Natalia; Felizia Arni Rudiawarni (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: This study investigates the effect of board size, institutional ownership, insolvency risk, and the COVID-19 pandemic on financial distress. This study differs from previous studies because it analyzes financial distress in COVID-19. This study also analyzes the impact of COVID-19 on financial distress for each sector on the Indonesia Stock Exchange.Method: This research applies logistic regression analysis. This study uses data from the financial and annual reports of companies listed on the Indonesia Stock Exchange, which are non-financial sectors from 2018 to 2020. This research covers 1,310 firm years as the object of study.Finding: This study finds that board size and institutional ownership can reduce financial distress risk by carrying out a monitoring function. Higher levels of debt increase the company's insolvency risk, resulting in a higher probability of the company experiencing financial distress. In addition, insolvency risk and the COVID-19 pandemic also influence financial distress, especially for property, real estate, construction building and trade, services, and investment sectors.Novelty: This research enriched the literature by finding out about the impact of the COVID-19 pandemic on financial distress. This research provides new insight regarding the influence of board size, institutional ownership, and insolvency risk on the probability of financial distress by considering the COVID-19 pandemic – the recent conditions when this research was conducted. This study also complements a sector-by-sector analysis that has not been done in previous studies on financial distress during the crisis.